2015
DOI: 10.1177/0731684415584431
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of hybrid glass/kenaf fibre-reinforced epoxy composite with matrix modification using liquid epoxidised natural rubber

Abstract: The hybridisation of natural fibre with glass fibre provides a method to improve the mechanical properties instead of using the natural fibres alone. This research is focused on the hybridisation of glass/kenaf fibre with the addition of liquid epoxidised natural rubber to enhance the desired mechanical properties of the composite by reducing the synthetic fibre usage and encourage the natural fibre consumption. Liquid epoxidised natural rubber was added to the epoxy matrix in order to improve its mechanical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…LENR was added to a hybrid glass/kenaf fiber‐reinforced epoxy composite in order to boost the mechanical properties of the hybrid composite closer to that of the solely glass fiber‐reinforced epoxy. And, indeed, addition of LENR increased impact strength by 40%, flexural strength by 13%, and flexural modulus by 15% . The success of the LENR showed that a mix of synthetic and natural fibers could be used for commercial applications along with the strengthening addition of LENR.…”
Section: Bio‐based Epoxy Resinsmentioning
confidence: 93%
“…LENR was added to a hybrid glass/kenaf fiber‐reinforced epoxy composite in order to boost the mechanical properties of the hybrid composite closer to that of the solely glass fiber‐reinforced epoxy. And, indeed, addition of LENR increased impact strength by 40%, flexural strength by 13%, and flexural modulus by 15% . The success of the LENR showed that a mix of synthetic and natural fibers could be used for commercial applications along with the strengthening addition of LENR.…”
Section: Bio‐based Epoxy Resinsmentioning
confidence: 93%
“…Tensile strength, flexural strength and impact strength of Sisal fiber-Ceramic Fiber Wool-Glass fiber with Epoxy resin is more than Aloe Vera-Ceramic Fiber Wool-Glass fiber with Epoxy resin. Muhammad et al [21] studied the mechanical properties of hybrid glass/Kenaf fiber-reinforced epoxy composite with the matrix modification using Liquid Epoxidized Natural Rubber (LENR) as a toughing agent. The results showed that the hybridization of Kenaf fiber with the glass fibre could produce better composite…”
Section: Mechanical Properties Of Natural and Synthetic Fiber Based Hybrid Polymer Compositesmentioning
confidence: 99%
“…The processing and fabrication of kenaf fiber composites lead to the fracture and damage of the composite structures. As such, kenaf fiber composites are always modified with other materials called fillers [ 1 , 2 , 5 , 6 , 7 , 8 , 9 , 10 ]. The combination of kenaf fiber with fillers or its hybridization with other types of reinforcing fibers could be very cost-effective and enhance the mechanical performance of the kenaf fiber composites.…”
Section: Introductionmentioning
confidence: 99%